Chronotope of Russian Works about Robinson - T. V. Shvetsova; V. E. Shakhova (Научный диалог)
The results of the study of the chronotope in Russian-language compositions based on the novel about Robinson’s adventures are presented. The material for the work was A. E. Razin’s novel “The Real Robinson” (1860) and Lev Tolstoy’s story “Robinson” (1862). The issues of the specifics of the representation of the chronotopic in the works of Russian writers are considered. The relevance of the study is due to the appeal to the universal of the chronotope, which contains an exhaustive toolkit for the artistic embodiment of images of space and time; as well as the search for new methods of literary analysis of the text. It is shown that in the analyzed texts, a kind of fusion of Russianlanguage compositions with a foreigncultural text in the aspect of a chronotope is realized. The similarities and differences in the rethinking of the story of Robinson are shown on the example of the model of textual connexity, the national specifics of the representation of the image of Robinson are indicated. It is noted that the external and internal chronotopes are retransmitted from work to work and create the basis for the emergence of the author’s intentions. It is proved that chronotopic analysis allows one to form an idea of the peculiarities of the Russian-language interpretation of the story of Robinson.